HPLC-UV profile of Genista ulicina Spach. (Fabaceae) extracts and in vitro antioxidant activity - Kaoutar Chebbah; Eric Marchioni; Djamel Sarri; Ahmed Menad; Ratiba Mekkiou; Ramdane Seghiri; Ouahiba Boumaza; Samir Benayache; Fadila Benayache (International Journal of Phytomedicine, 2016)
To perform a qualitative and quantitative analysis of the phenolic and flavonoid contents and evaluate the antioxidant activity of ethyl acetate (EtOAc) and n-butanol (n-BuOH) extracts of the aerial parts of Genista ulicina Spach. from Algeria. The qualitative analysis of plant extracts was carried out by RP-HPLC using UV detector, whereas the quantification of total phenolic and flavonoid contents was completed according to the Folin-Ciocalteu procedure and aluminium chloride colorimetric method respectively. To evaluate the extract’s antioxidant activity, Two in vitro antioxidant tests were employed: DPPH and β-carotene bleaching assay. The HPLC/DAD chromatogram showed several peaks indicating the presence of phenolic acids, flavonoids and isoflavonoids in both extracts. The total phenolic content (TPC) ranged from 62.56 and 50.45 mgGAE/g extract, while the total flavonoids content varied between 53.1 and 48.4 mgQE/g extract for EtOAC and n-BuOH respectively. EtOAc extract showed a maximum inhibition value (78.15%) at 150µg/mL using DPPH test and highest antioxidative power (82.42%) using β-carotene bleaching assay comparing with standards. The HPLC-UV analysis showed the richeness of both extracts in phenolic and flavonoid contents. The EtOAc extract exhibited good antioxidant activities comparing to the n-BuOH extract. Thus Genista ulicina could be indicated as a plant of phytopharmaceutical importance.